Assessment of trace metal levels in size-resolved particulate matter in the area of Leipzig. (March 2018) - Fomba, Khanneh Wadinga; van Pinxteren, Dominik; Müller, Konrad; Spindler, Gerald; Herrmann, Hartmut
Abstract: Size-resolved trace metal concentrations at four sites in Leipzig (Germany) and its surrounding were assessed between the winter of 2013 and the summer of 2015. The measurements were performed in parallel at; traffic dominated (Leipzig – Mitte, LMI), traffic and residential dominated (Eisenbahnstrasse, EIB), urban background (TROPOS, TRO) and regional background (Melpitz, MEL) sites. In total, 19 trace metals, i.e. K, Ca, Ti, Mn, Fe, Cu, Zn, As, Se, Ba, V, Pb, Ni, Cr, Sr, Sn, Sb, Co and Rb were analysed using total reflection x-ray fluorescence (TXRF). The major metals were Fe, K and Ca with concentrations ranging between; 31–440 ng/m 3, 42–153 ng/m 3 and 24–322 ng/m 3, respectively, while the trace metals with the lowest concentrations were Co, Rb and Se with concentrations of; < 0.3 ng/m 3, <0.5 ng/m 3 and 0.5–0.7 ng/m 3, respectively. PM10 trace metal concentrations during easterly air mass inflow especially at the background sites were in average 70% higher in the winter and 30% higher in the summer in comparison to westerly air mass inflow. Traffic at LMI contributed to about 75% of Cr, Ba, Cu, Sb, Sn, Ca, Co, Mn, Fe and Ti concentrations while regional activities contributed to more than 70% of K, Rb, Pb, Se, As and V concentrations. Traffic dominated trace metals were often observed in the coarse mode while the regional background dominated trace metals were often observed in the fine mode. Trace metal sources were related to crustal matter and road dust re-suspension for metals such as Ca, Fe, Co, Sr, and Ti, brake and tire wear (Cu, Sb, Ba, Fe, Zn, Pb), biomass burning (K, Rb), oil and coal combustion (V, Zn, As, Pb). Crustal matter contributed 5–12% in winter and 8–19% in summer of the PM10 mass. Using Cu and Zn as markers for brake and tire wear, respectively, the estimated brake and tire wear contributions to the PM10 mass were 0.1–0.8% and 1.7–2.9%, respectively. The higher contributions were observed at the traffic sites while the lower contributions were observed at the regional background site. In total, non-exhaust emissions could account for about 10–22% of the PM10 mass in the summer and about 7–15% of the PM10 mass in the winter. Highlights: Size-resolved trace metal levels were assessed at traffic, urban and regional sites. Sources were traffic, crustal matter, biomass burning and coal combustion. Cu and Zn were used as markers to estimate brake and tire wear, respectively. Brake and tire wear contributed up to 0.8% and 2.9%, respectively, to the PM10 mass. Non-exhaust emissions contributed up to 22% (summer) and 15% (winter) to PM10.